Smoking status during first‐line immunotherapy and chemotherapy in NSCLC patients: A case–control matched analysis from a large multicenter study. Issue 6 (1st February 2021) - Cortellini, Alessio; De Giglio, Andrea; Cannita, Katia; Cortinovis, Diego L.; Cornelissen, Robin; Baldessari, Cinzia; Giusti, Raffaele; D'Argento, Ettore; Grossi, Francesco; Santoni, Matteo; Catino, Annamaria; Berardi, Rossana; et al.
Abstract: Background: Improved outcome in tobacco smoking patients with non‐small cell lung cancer (NSCLC) following immunotherapy has previously been reported. However, little is known regarding this association during first‐line immunotherapy in patients with high PD‐L1 expression. In this study we compared clinical outcomes according to the smoking status of two large multicenter cohorts. Methods: We compared clinical outcomes according to the smoking status (never smokers vs. current/former smokers) of two retrospective multicenter cohorts of metastatic NSCLC patients, treated with first‐line pembrolizumab and platinum‐based chemotherapy. Results: A total of 962 NSCLC patients with PD‐L1 expression ≥50% who received first‐line pembrolizumab and 462 NSCLC patients who received first‐line platinum‐based chemotherapy were included in the study. Never smokers were confirmed to have a significantly higher risk of disease progression (hazard ratio [HR] = 1.49 [95% CI: 1.15–1.92], p = 0.0022) and death (HR = 1.38 [95% CI: 1.02–1.87], p = 0.0348) within the pembrolizumab cohort. On the contrary, a nonsignificant trend towards a reduced risk of disease progression (HR = 0.74 [95% CI: 0.52–1.05], p = 0.1003) and death (HR = 0.67 [95% CI: 0.45–1.01], p = 0.0593) were reported for never smokers within the chemotherapy cohort. After a random case–control matching, 424 patients from both cohorts were paired. Within the matched pembrolizumab cohort, never smokers had a significantly shorter progression‐free survival (PFS) (HR = 1.68 [95% CI: 1.17–2.40], p = 0.0045) and a nonsignificant trend towards a shortened overall survival (OS) (HR = 1.32 [95% CI: 0.84–2.07], p = 0.2205). On the contrary, never smokers had a significantly longer PFS (HR = 0.68 [95% CI: 0.49–0.95], p = 0.0255) and OS (HR = 0.66 [95% CI: 0.45–0.97], p = 0, 0356) compared to current/former smoker patients within the matched chemotherapy cohort. On pooled multivariable analysis, the interaction term between smoking status and treatment modality was concordantly statistically significant with respect to ORR ( p = 0.0074), PFS ( p = 0.0001) and OS ( p = 0.0020), confirming the significantly different impact of smoking status across the two cohorts. Conclusions: Among metastatic NSCLC patients with PD‐L1 expression ≥50% receiving first‐line pembrolizumab, current/former smokers experienced improved PFS and OS. On the contrary, worse outcomes were reported among current/former smokers receiving first‐line chemotherapy. Abstract : Improved outcome in tobacco smoking NSCLC patients following treatment with immune checkpoint inhibitors (ICIs) has previously been reported. Little is known regarding this association during first‐line immunotherapy in patients with high PD‐L1 expression. Clinical outcomes according to the smoking status of two large multicenter cohorts were compared in this study. Smokers with high PD‐L1 expression ≥ 50% experienced improved progression‐free survival (PFS) and overall survival (OS) with first‐line pembrolizumab. The opposite trend was found in NSCLC patients treated with first‐line platinum‐based chemotherapy.